Associations among sexuality-related factors, recent two-week morbidity and annual hospitalization in female migrant workers: a cross-sectional study in southern China. Issue 8 (14th September 2021) - Su, Zhen-Zhen; Li, Bing-Bing; Li, Bo; Wu, Yan-Yan; Fu, Li-Ying; Wu, Xiao; Wang, Pei-Xi
ABSTRACT: To explore the influence of sexuality-related factors on recent two-week morbidity and annual hospitalization in female migrant workers, 880 Chinese rural-to-urban female migrant workers aged 16–57 years were studied. Clustered logistic regression analyses revealed that women who never or seldom experienced lubrication difficulties had a lower risk of recent two-week morbidity (adjusted odds ratio [OR] = 0.32, 95% confidence interval [CI] = 0.17–0.60, P < 0.001; adjusted OR = 0.35, 95% CI = 0.18–0.69, P = 0.003) than those who always experienced lubrication difficulties; women who never felt a lack of sexual interest had a significantly lower risk of annual hospitalization (adjusted OR = 0.40, 95% CI = 0.20–0.79, P = 0.009) than those who always or seldom lacked sexual interest, and women who never felt sexual satisfaction had a higher risk of annual hospitalization (adjusted OR = 3.08, 95% CI = 1.75–5.42, P < 0.001) than those who always or seldom experienced sexual satisfaction. The independent contributions of sexuality-related factors to the risk of recent two-week morbidity and annual hospitalization were 5.8% and 29.5%, respectively. This study suggests that sexuality may have a modest influence on recent two-week morbidity and a dominant impact on annual hospitalization.